2002
DOI: 10.1038/sj.ijir.3900812
|View full text |Cite
|
Sign up to set email alerts
|

Intracavernous injections for erectile dysfunction in patients with cardiovascular diseases and failure or contraindications for sildenafil citrate

Abstract: The aim of this study was to evaluate the effectiveness of a progressive program for the treatment of erectile dysfunction in patients with cardiovascular disease in whom sildenafil citrate (Viagra) was not an option. The study population included 106 patients selected from 267 with cardiovascular disease. The intracavernous injection program consisted of three protocols of increasingly complex combinations of vasoactive drugs, papaverine, phentolamine, prostaglandin E1 and atropine sulfate. Patients who faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…This is in contrast to the reported incidence of pain in some studies (3.5%) 7 and on the other hand is comparable with or even lower than others (12.5-34.4%). 6,12 A probable explanation for the high incidence of pain in our study is that apprehension of the needle aggravates pain. As the process of titration and home injection is continued, the patient's fears decrease and the actual pain related to the drug and not to the injection becomes apparent.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is in contrast to the reported incidence of pain in some studies (3.5%) 7 and on the other hand is comparable with or even lower than others (12.5-34.4%). 6,12 A probable explanation for the high incidence of pain in our study is that apprehension of the needle aggravates pain. As the process of titration and home injection is continued, the patient's fears decrease and the actual pain related to the drug and not to the injection becomes apparent.…”
Section: Discussionmentioning
confidence: 93%
“…20 The incidence of priapism for Tx varies between 0 and 3.7%. 7,12,21 This variability in incidence is expected because of the different doses of papaverine used and different definitions for priapism. With Tx, our study showed that the overall incidence of priapism is 5%, which is significantly higher than PgE 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Other side effects of intracavernous combination therapy include injection site bruising, subcutaneous hemorrhage, and prolonged erection. [2][3][4][5][6] Dose-dependent fibrotic reactions presenting as penile nodules, plaques, or induration may also occur. [2][3][4][5][6] The only reported systemic side effects are elevated liver enzymes, arterial hypotension, and headache.…”
Section: Brief Reportsmentioning
confidence: 99%
“…[2][3][4][5][6] Dose-dependent fibrotic reactions presenting as penile nodules, plaques, or induration may also occur. [2][3][4][5][6] The only reported systemic side effects are elevated liver enzymes, arterial hypotension, and headache. [2][3][4][5][6]11 Since side effects are generally mild and infrequent, intracavernous injection therapy has been deemed safe and effective in the treatment of erectile dysfunction.…”
Section: Brief Reportsmentioning
confidence: 99%